Naucno-technologiceskoe obosnovanie standartnoj ucebno-trenirovocnoj programmy u detej mladsego skol'nogo vozrasta - Apokin, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The main purpose of this research was the theoretical substantiation and experimental check of an opportunity of the use of the standard educational-training program of stimulated development of speed in the sensitive period of 9-10 years pupils in the conditions of physical culture lessons at school.